1990
DOI: 10.1037/0022-3514.58.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal affect responses to male and female leaders: Implications for leadership evaluations.

Abstract: It was hypothesized that female leaders would elicit more negative nonverbal affect responses from other group members than male leaders offering the same initiatives. Male and female subjects participated in 4-person discussions in which male or female confederates assumed leadership. During the discussion subjects' nonverbal affect responses to the confederates were coded from behind oneway mirrors. Female leaders received more negative affect responses and fewer positive responses than men offering the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(154 citation statements)
references
References 73 publications
6
144
0
3
Order By: Relevance
“…Heilman et al, 11 in a randomized study where evaluators rated assistant vice presidents for identical accomplishments, found that women but not men who were competent in leadership positions typically held by men were viewed as unlikable and that competence and likability were independent predictors of being recommended for institutional rewards. Butler and Geis 17 found that when women perform as a single leader in a work group, they are subject to more subtle negative affective responses from other members of the team than men following identical scripts. The negative consequences for women in the corporate world who lead with a style associated with male gender schema have even led to the creation of workshops called Bully Broads to teach capable high-ranking women how to assume more socially acceptable, stereotypically female communal behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heilman et al, 11 in a randomized study where evaluators rated assistant vice presidents for identical accomplishments, found that women but not men who were competent in leadership positions typically held by men were viewed as unlikable and that competence and likability were independent predictors of being recommended for institutional rewards. Butler and Geis 17 found that when women perform as a single leader in a work group, they are subject to more subtle negative affective responses from other members of the team than men following identical scripts. The negative consequences for women in the corporate world who lead with a style associated with male gender schema have even led to the creation of workshops called Bully Broads to teach capable high-ranking women how to assume more socially acceptable, stereotypically female communal behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when women behave in a more stereotypically masculine way, it may trigger negative reactions. 9,17,18 Performing a meta-analysis of experimental studies in which only the sex of the leader varied, Eagly et al 19 found that women leaders who adopted a stereotypically masculine, autocratic style received lower evaluations than men exhibiting the same style of leadership. Heilman et al, 11 in a randomized study where evaluators rated assistant vice presidents for identical accomplishments, found that women but not men who were competent in leadership positions typically held by men were viewed as unlikable and that competence and likability were independent predictors of being recommended for institutional rewards.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the competent task contributions of women are more likely to be ignored or to evoke negative reactions than those of men (Altemeyer & Jones, 1974;Ridgeway, 1978Ridgeway, , 1981Ridgeway, , 1982. Also, women who genuinely exert influence are less likely to be liked or recognized as influential than men who exert influence (Butler & Geis, 1990;Walker et al, 1996).…”
Section: Less Favorable Evaluation Of Women's (Than Men's) Agentic Bementioning
confidence: 99%
“…Butler and Geis ( 1990 ) used experimental approaches to examine the role of gender and leadership in the reactions of observers. They focused on nonverbal responses-in particular, positive or negative facial reactions of participants who observed leaders making suggestions for certain courses of action.…”
Section: Role Incongruity and Leadership In Large Classesmentioning
confidence: 99%